WOOD CALORIFIC POWER FROM Eucalyptus grandis AND Hevea brasiliensis SPECIES - Müzel, S. D.; De Oliveira, K. A.; Hansted, F. A. S.; Prates, G. A.; Goveia, D. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Biomass is all organic material, which when burned, releases some form of energy. In order to characterize biomass burning is becomes necessary to know its calorific value that is directly related to the moisture content on the fuel. The objective of this study is to determine the high heating value from particles of the species Eucalyptus grandis and Hevea brasiliensis, aiming to know its energy potential. To accomplish this it was determined the moisture content by gravimetric method, and the high heating value was determined by an isothermal calorimeter Ika bomb. The results for moisture content were satisfactory compared with those recommended by the NBR 14929 (2003), DIN 51731 and ÖNORM M7135, and as the high heating calorific value was considered appropriate and for what it is worth greater than the usual values found in literature, therefore this material has proved to have a good power potential and can be used for burning, and also on power generation.